2019
DOI: 10.31986/issn.2578-3343_vol1iss1.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Diversity in Mindfulness Research on Health: A Narrative Review using the ADDRESSING Framework

Abstract: INTRODUCTIONOver the past 5 years, the number of Americans practicing meditation has more than tripled, rising from 4% of adults in 2010 to 14% in 2017. 1 This rise is likely related to the increasing focus on preventive and integrative approaches to healthcare in the United States, such as meditation, whih is often used to reduce stress, anxiety, depression, and pain in conjunction with improving health and well-being. 2 While many different meditative practices exist, mindfulness meditation emphasizes nonjud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…In addition, individuals who reported higher baseline anxiety and greater sleep quality complaints experienced greater decreases in stress-related physical symptoms, and individuals reporting higher baseline anxiety had greater improvements in cognitive reappraisal; these benefits did not differ by gender. Previous literature that looked at gender differences during MBSR treatment found similar results, where the populations were predominantly women, but both men and women reported significant improvements in health outcomes post-treatment (Chin et al, 2019). Together with existing data, the present study demonstrates the effectiveness of MBSR and other MBI’s for populations with elevated symptoms of anxiety and sleep disturbance.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, individuals who reported higher baseline anxiety and greater sleep quality complaints experienced greater decreases in stress-related physical symptoms, and individuals reporting higher baseline anxiety had greater improvements in cognitive reappraisal; these benefits did not differ by gender. Previous literature that looked at gender differences during MBSR treatment found similar results, where the populations were predominantly women, but both men and women reported significant improvements in health outcomes post-treatment (Chin et al, 2019). Together with existing data, the present study demonstrates the effectiveness of MBSR and other MBI’s for populations with elevated symptoms of anxiety and sleep disturbance.…”
Section: Resultsmentioning
confidence: 62%
“…Limitations included reliance on self-report measures, lack of a control group, possible expectancy effects associated with paying to take the MBSR program, and a primarily female, Caucasian, high socioeconomic status sample. Nevertheless, the current findings are among the first to directly compare MBSR outcomes for women and men in the same program, while also examining the interaction between gender and baseline distress levels in predicting MBSR outcomes, thereby advancing a nascent field trying to better address diversity issues in mindfulness research (Chin et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 69 MBI RCTs conducted in the United States reported an oversampling of white, higher SES women: ¾ of participants were white, 70% were women, and participants’ educational attainment and income were higher than US averages ( Waldron et al., 2018 ). Thus, whether MBIs are acceptable and salubrious in populations underrepresented in research is a critical question ( Chin et al., 2019b ). Importantly, lower SES and racial minority status are associated with elevated inflammation and poorer health in part through stress exposure that often begins in childhood ( Williams et al., 1997 ).…”
Section: What Are Mbis?mentioning
confidence: 99%
“…Importantly, there is a lack of knowledge as to the feasibility, acceptability, and efficacy of mindfulness-based approaches designed to target the unique stressors, health needs, and values of diverse populations. It is essential that the next wave of mindfulness research address “the potential health benefits of mindfulness across diverse, underrepresented, and medically underserved communities” (Chin et al, 2019, p. 9), and how to reduce barriers that limit accessibility of mindfulness to these vulnerable groups .…”
mentioning
confidence: 99%